Acetic Acid Bacteria in Sour Beer Production: Friend or Foe? - Bouchez, Arne; De Vuyst, Luc (Frontiers in Microbiology, 2022)
Beer is the result of a multistep brewing process, including a fermentation step using in general one specific yeast strain. Bacterial presence during beer production (or presence in the beer itself) is considered as bad, since bacteria cause spoilage, produce off-flavors, and/or turbidity. Although most problems in the past related to lack of hygiene and/or cleaning, bacteria do still cause problems nowadays. Despite this negative imago, certain bacteria play an irreplaceable role during fermentation and/or maturation of more unique, funky, and especially refreshing sour beers. The term sour beers or sours is not restricted to one definition but covers a wide variety of beers produced via different techniques. This review proposes an uncluttered sour beer classification scheme, which includes all sour beer production techniques and pays special attention to the functional role of acetic acid bacteria. Whereas their oxidation of ethanol and lactate into acetic acid and acetoin usually spoils beer, including sour beers, organoleptically, a controlled growth leads to a desirable acidic flavor in sour beers, such as lambic-style, lambic-based, and red-brown acidic ales.